Recovery of waste cooking palm oil as a crosslinker for inverse vulcanized adsorbent to remove iron (Fe3+) ions - Nayeem, Abdullah; Mohd Faizal, Ali; Jun Haslinda, Shariffuddin (Elsevier Ltd, 2024)
Gas and oil reservoirs around the world leave megatons of unused elemental sulfur as industrial byproducts which has been successfully used in inverse vulcanization. We reported the successful application of inverse vulcanized porous adsorbent from waste cooking palm oil (WCO) to remove ferric (Fe3+) ions. Sodium chloride (NaCl) acted as a porogen to get the porous polysulfide. The removal of Fe3+ was observed through the atomic absorption spectroscopic (AAS) technique. The effects of pH (3,7, and 11) and initial concentration (35, 40, 45 mg/L) of Fe3+ solution, and dosage (10, 15, and 20 g/100mL) on Fe3+ adsorption were studied to determine the best removal condition. Later, fixing the best parameters (pH 3, 40 mg/L, 20 g/100mL), Langmuir and Freundlich equations were used to study the adsorption isotherm. Adsorption kinetics were described using linear and nonlinear pseudo-first and second-order reactions. The Freundlich isothermal model and linear pseudo- second-order kinetics fit best for the removal process. The comparison between the pre and post-adsorption analyses using FTIR, SEM-EDX, and the isothermal model confirmed the physisorption of Fe3+. The current study concluded with some further scopes of the adsorbent for diverse removal applications.